مظاهر الوسطية وتطبيقاتها في منظور القرآن والسنة = The manifestations of moderation and its applications in the perspective of the Qur’an and Sunnah - Atohame, Njea Husean; Youssef, Mohamed Abdelrahman Ibrahim (Nouakchott Modern University, Mauritania, 2023)
The issue of moderation is a matter of great destiny, of great interest, of great interest, and wide scope. And because its vast aspects cannot be fulfilled in such a short research, therefore, according to the researcher, you should refer to features of it in the three aspects: social, political and economic, because the Islamic nation - especially in its contemporary state - is living in apparent weakness in many of its conditions, and from The manifestation of weakness lies in these three aspects And the moderation is the middle path in which to trace the trail, and to show the straight path until it becomes evident that the exaggerated excesses, the impersonation of the invalid, If we consider the title of this research, we will find that what is meant is a sentence: the rooting of the moderate approach to which our true religion advocated and approved by the purified Sunnah through its application in the economic, social and political aspects.